KURIKULUM MUATAN LOKAL DALAM MENINGKATKAN KUALITAS PELAYANAN DI SDIT AL-ISLAM SINE - Luluk Muasomah (Institut Agama Islam Ngawi, 2022)
Abstract Since the Middle Ages, science has developed rapidly. The period after the Middle Ages is often called the modern era. The development of science is based on the discoveries and thoughts of ancient philosophers. The results showed that the Local Content Curriculum at SDIT Al Islam Sine was not centered on the National Curriculum; (Kurnas), but there is an increase in local content and is in the formulation team. The planning system is implemented by analyzing the volume and workload which they call Tupoksi (Main Tasks and Functions). This study aims to reveal whether there are differences between schools that implement local content curriculum and schools without local content. This research is a quantitative research by taking samples from students of SDIT Al Islam with observation, documentation and interviews who participated in the memorization of akhlakul karimah activities and were declared good. The local content (Mulok) at SDIT Al Islam was centered on students who had additional material desires. The evaluation system is implemented on two (2) targets, namely: evaluation of student travel per semester and evaluation of the program implementers themselves.Keywords: Local Content Curriculum, Education Quality, SDIT Al-Islam Sine